2011
DOI: 10.1002/term.397
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of methods for the construction of collagenous scaffolds with a radial pore structure for tissue engineering

Abstract: Type I collagen is used widely as a biomaterial. The structure of collagenous biomaterials, including pore sizes and general architecture, can be varied by a number of techniques. In this study, we developed a method to construct flat fibrillar type I collagen scaffolds, 6 cm in diameter and with a radially orientated pore structure, by the use of directional freezing. Different methodologies were tested, the optimal one being freezing of a collagen suspension inside-out, using a centrally positioned liquid ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 13 publications
1
25
0
2
Order By: Relevance
“…Conforming to our expectations, the radially oriented structure exhibited a predetermined 3-D shape, as well as suitable porosity and micromechanical properties. Brouwer and colleagues designed a twolayered collagenous scaffold with a radial pore structure for repair of the diaphragm, and found that cells infiltrate further into the center of the scaffold [24,39]. This is consistent with our results that BMSCs were recruited into the radially oriented scaffold.…”
Section: Discussionsupporting
confidence: 94%
“…Conforming to our expectations, the radially oriented structure exhibited a predetermined 3-D shape, as well as suitable porosity and micromechanical properties. Brouwer and colleagues designed a twolayered collagenous scaffold with a radial pore structure for repair of the diaphragm, and found that cells infiltrate further into the center of the scaffold [24,39]. This is consistent with our results that BMSCs were recruited into the radially oriented scaffold.…”
Section: Discussionsupporting
confidence: 94%
“…They found that cells infiltrated further into the center of the scaffold. Besides, Brouwer and his colleagues also designed a scaffold with radial pore structure to repair the diaphragm defects, and reached the same conclusion [92, 93]. The in vivo experiments on rabbits confirmed that BMSCs could also be recruited into the radially-oriented scaffold with the assistance of SDF-1α.…”
Section: Applicationsmentioning
confidence: 80%
“…It is also important for tissue tensile strength and for forming a functional scaffold for cells. 14 Because of its unique characteristics, 15 collagen is widely used as a biomaterial, scaffold, and culture substrate for cell and tissue regeneration. 10 Type I collagen plays an essential part in the regulation of cellular behavior.…”
Section: Introductionmentioning
confidence: 99%